Simulasi Envi-Met Kenyamanan Termal Jalur Pejalan Kaki di Jalan Jenderal Sudirman, Yogyakarta - Prasetyo Febriarto; RR. Sophia Ratna Haryati; Muhammad Zaki (Universitas Muslim Indonesia, 2023)
The effects of a humid tropical climate affect urban development activities which result in the emergence of urban heat islands. This phenomenon has an impact on activities that occur in the pedestrian path of Jalan Jenderal Sudirman, Yogyakarta. The effect of a heat island that is most felt by humans is heat or rising temperatures which will affect human activity, namely thermal comfort. This research is focused on the thermal comfort of the microclimate of the pedestrian path of Jalan Jenderal Sudirman, Yogyakarta. The problem is how far the heat island affects the physical thermal comfort of urban development. The research objective is to provide an overview of the thermal comfort of the microclimate of pedestrian paths. The research was conducted using the Envi-MET 3.1 software simulation method and empirical measurements. The stages of the research were the preparatory stages in the form of an initial survey, data collection primary and secondary, the stages of analysis namely modeling simulations using Envi-Met software, and using Leonardo to provide visualization then converted into thermal comfort standards. The results of this study are Envimet simulation results and vegetation are supporting elements that can provide the main comfort related to outdoor thermals.